2021
DOI: 10.1186/s12989-021-00407-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to PM2.5 aggravates SLE manifestations in lupus-prone mice

Abstract: Background Air pollution causes negative impacts on health. Systemic lupus erythematosus (SLE) is an autoimmune disease with diverse clinical manifestations and multifactorial etiology. Recent studies suggest that air pollution can trigger SLE and induce disease activity. However, this association has not been deeply investigated. Thus, the aim of this study was to evaluate whether exposure to fine particulate matter (PM2.5) exacerbates SLE manifestations, focusing on renal complications, in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Exposure to PM2.5 also caused kidney inflammatory cells infiltrated, glomerular necrosis, and structure anomalies (Xu, Qin, et al, 2018); collagen accumulation (Chenxu et al, 2018); decreased tubular lumen and glomerular volumes; and increased BUN, mesangial expansion, and even fibrosis, which was more severe in hypertensive animals than in healthy animals, suggesting that hypertensive individuals are more susceptible to PM2.5 than those healthy (Tavera Busso et al, 2018). In addition, Yariwake et al (2021) found female NZBW mice with concentrated ambient particles exposure (CAP) showed increased circulating neutrophils and kidney weight with renal cortex enlargement, decreased survival, and early appearance of proteinuria comparing to NZBW mice with FA exposure.…”
Section: Pm25 Exposure Induces Kidney Injury: Evidence From In Vivo S...mentioning
confidence: 99%
“…Exposure to PM2.5 also caused kidney inflammatory cells infiltrated, glomerular necrosis, and structure anomalies (Xu, Qin, et al, 2018); collagen accumulation (Chenxu et al, 2018); decreased tubular lumen and glomerular volumes; and increased BUN, mesangial expansion, and even fibrosis, which was more severe in hypertensive animals than in healthy animals, suggesting that hypertensive individuals are more susceptible to PM2.5 than those healthy (Tavera Busso et al, 2018). In addition, Yariwake et al (2021) found female NZBW mice with concentrated ambient particles exposure (CAP) showed increased circulating neutrophils and kidney weight with renal cortex enlargement, decreased survival, and early appearance of proteinuria comparing to NZBW mice with FA exposure.…”
Section: Pm25 Exposure Induces Kidney Injury: Evidence From In Vivo S...mentioning
confidence: 99%
“…Twenty mice of the New Zealand Black White F1 strain were used (NZBWF1), an animal model in which SLE develops spontaneously. Mice were acquired from the research institution The Jackson Laboratory (https://www.jax.org), these animals come from a previously published study, in which the focus of the study was the renal system [17]. Young animals were used, exposed or not to pollution (PM2.5) during the 4-month period (n=10/group).…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Usually, air pollution has been shown to be a key factor in the generation of autoimmune diseases and their increased severity ( Figure 4 ) [ 26 , 27 , 28 ]. In another study, it was shown that among the different environmental pollutants, ozone was the only one to remain constant regardless of the season of the year, in relation to the risk of relapse in multiple sclerosis [ 29 ].…”
Section: Regulatory T Cells and Diseasementioning
confidence: 99%